Profile and Outcome of Patients Admitted to Pediatric Intensive Care Unit at a General Referral Hospital - Sharma, Arun K; Gurung, Binay (Journal of Institute of Medicine Nepal, 2019)
Introduction Nepal has made substantial progress in child health primarily through preventive care. There is an increasing need for critical care services across the country which is highly resource-intensive. Periodic data of critical care admissions help plan the utilization of scarce resources in a low-income country like Nepal. This study aimed to analyze the epidemiologic patterns of critically ill pediatric patients admitted to the pediatric intensive care unit (PICU). Methods This descriptive study of all children admitted to PICU at Tribhuvan University Teaching Hospital for 18 months between October 2017 and April 2019 was conducted by a retrospective review of hospital records. Demographic data, etiologies of PICU admissions and outcomes of children admitted to the PICU were analyzed. Results PICU admitted 413 children during the study duration from all over the country. Children under the age of 2 years (36%) were admitted in the largest number and boys outnumbered girls (65.1%). Respiratory illnesses, neurosurgical and neurological problems, infectious disorders and airway foreign bodies were the most common etiologies for admission. The average length of ICU stay was around 4.4 days. Almost one-third of patients required circulatory and respiratory support. At the time of exit from PICU, 14.3% of patients died; 4.3% patients had opted for withdrawal of life support or decided to leave hospital against medical advice. Conclusion Patients with diverse etiologies were admitted to ICU from all over the country. A similar analysis from PICUs across the country can serve as the basis for development of newer intensive care facilities in the country, developing dedicated protocols for critical care and redistributing the ICUs’ available resources for optimal efficiency.